7-day post-vaccination efficacy of the CSF CL strain produced on ovine cell line against a virulent classical swine fever (Hog cholera) challenge - Risatti, Guillermo R. (2018)
Classical swine fever (CSF), also known as hog cholera, is a highly contagious viral disease classified as a notifiable (previously List A) pig disease by OIE. In an infected environment, vaccines are the basic tools for control and eradication of CSFV. This study aimed at assessing the efficacy of an attenuated CSF CL strain produced on ovine cells against a virulent CSF challenge performed 7 days post-vaccination. Material and methodsTwo groups of 8 CSF-negative crossbred pigs weighing 18 kg were either vaccinated with a live one dose of CL strain (>100 PD50/dose) or left unvaccinated. Seven days post-vaccination, they were challenged with 5.5log10TCID50 CSFV of Haiti-96 strain both intramuscularly and intranasally with separated aliquots. Clinical signs, rectal temperature were monitored for 28 days post-challenge (DPC) and necropsied. Blood samples, nasal swabs and tonsil scrapings were regularly collected and assayed for blood formulation, sera antibody titres (E2-Erms ELISAs, SN titrations), and viral loads in total blood, nasal and tonsil mucus. ResultsAll controls showed typical acute CSF justifying euthanasia on ethical ground 22 DPCH at the latest. They also developed severe leukopenia and lymphopenia. Necropsic lesions were evocative of chronic form of CSF. None of the vaccinates developed any sign of CSF.CSFV was detected in controls from 4DPC in blood plateauing close to 6log10TCID50/mL. CSFV was detected in nasal and tonsillar mucus from 8DPC reaching up to 4.8log10TCID50/mL. Vaccinates showed no detectable CSFV in any sample post-challenge.All pigs were antibody negative before challenge. A seroneutralizing anamestic reaction was evidenced as early as 7DPC in all vaccinates whereas ELISA antibody titres turned positive slower. Serological response to challenge was almost absent in controls. Discussion and conclusionViral circulation in herds relies mainly on direct nose-to-nose contacts and in-utero transmission. The ability of vaccines to limit CSFV transmission is vital for control and eradication strategies. Under the conditions of the study, the CL strain was able to totally prevent CSF and totally abolished both CSFV viremia and mucosal shedding as early as 7 days post-vaccination, thus showing its relevance for whole herd strategies. Additionally, it was noticed that ELISA correlated poorly with protection.